1996
DOI: 10.1074/jbc.271.31.18859
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Cloning of Centaurin-α

Abstract: Using an affinity resin and photoaffinity label based on phospholipid analogs of inositol 1,3,4,5-tetrakisphosphate (InsP 4 ), we have isolated, characterized, and cloned a 46-kDa protein from rat brain, which we have named centaurin-␣. Binding specificity was determined using displacement of 1-O- Receptor-stimulated phosphoinositide (PI) 1 metabolism generates numerous inositol polyphosphates (InsP n s) and inositol phospholipids, many of which may function as potential second messengers (1). Of the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
73
0
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 150 publications
(80 citation statements)
references
References 70 publications
6
73
0
1
Order By: Relevance
“…Uncertainties concerning the effective concentration of inositol lipids under these conditions, and the contributory effects of the micelle itself, both hinder the interpretation of any effects that may be observed. To combat this problem, there has been an increasing use of water-soluble analogues of the inositol lipids, which has led to some important, quantitative information on their actions (17,30,35,36). We also adopted this approach.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainties concerning the effective concentration of inositol lipids under these conditions, and the contributory effects of the micelle itself, both hinder the interpretation of any effects that may be observed. To combat this problem, there has been an increasing use of water-soluble analogues of the inositol lipids, which has led to some important, quantitative information on their actions (17,30,35,36). We also adopted this approach.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it prompted us to consider that AP-3 may share some sequence homologies with other PtdIns(3,4,5)P 3 -binding proteins. In this respect, the recent discovery of a novel PtdIns(3,4,5)P 3 -binding protein, centaurin-␣, has led to the identification of a putative consensus motif (PX [13][14] (R/K)X 4 (R/K)XKX 5 FX 6 E) for dictating the high affinity for the 3,4,5-trisphosphate cluster and which is shared by synaptotagmin and a protein (GAPInsP 4 -BP), which is a candidate for mediating Ca 2ϩ entry into cells (36). It is interesting that this motif is partly conserved by amino acids 32-51 (HX 5 KKKX 3 YX 6 E) within the 33-kDa amino-terminal domain of AP-3 (11), which is known to contain the polyphosphate binding site (9).…”
Section: Discussionmentioning
confidence: 99%
“…This observation in fact enabled the isolation and purification of centaurin-␣, a novel multi-domain protein with both homology regions, suggesting its role in communication of membrane lipid changes to the cytoskeleton (21). Very recently, the Nterminal region of the ␣ subunit of AP-2 was found to have high affinity for PIP 3 (38), a finding foreshadowed by the highly selective and efficient photoaffinity labeling of AP-2 by [ 3 H]BZDC-IP 4 (31,32).…”
Section: Photolabeling Of Different Domains Of Syt II and Syt Iii Witmentioning
confidence: 99%
“…For example, four IP 4 binding proteins were affinity-purified from rat brain (30) and photoaffinity labeled with [ 3 H]BZDC-IP 4 (22,31). Two have been further characterized; the ␣ subunit of clathrin assembly protein (AP-2) (32) had the highest affinity for IP 6 , whereas the novel cytoskeletal linker protein centaurin-␣ had the highest affinity for PIP 3 (21). The IP 3 binding site of the affinity-purified rat brain IP 3 receptor (19) has been identified by sequencing a proteolytic fragment of the [ 3 H]BZDC-IP 3 photoaffinity-labeled protein (33).…”
Section: Photolabeling Of Different Domains Of Syt II and Syt Iii Witmentioning
confidence: 99%
“…The resulting PtdIns(3,4,5)P 3 has been shown to increase rapidly and transiently in many cells in response to a wide variety of stimuli and since there are no known phospholipases that can metabolize this lipid (13), it has been suggested that PtdIns(3,4,5)P 3 itself is a second messenger. At present there are reports that PtdIns(3,4,5)P 3 can activate atypical forms of protein kinase C (14) and can bind to protein kinase B (also named Akt or Rac) (15)(16)(17) and the recently cloned centaurin (18), encoding for a novel gene, which is highly expressed in brain and which shows homology to yeast and mammalian Arf GTPase-activating proteins.…”
mentioning
confidence: 99%